From capacity building to local adoption: Manufacturing and diffusion of cassava flash dryers in DR Congo - Tran, Thierry; Taborda , Luis (2025)
Flash drying enhances cassava processing efficiency, reducing fuel consumption by 44% (from 132 to 74 liters/ton) and saving USD 60 per ton at current diesel prices (USD 1.036 per liter). Consistent drying lowers product rejection, boosting financial gains. Initially introduced through projects, local manufacturers are now independently producing flash dryers, with one training non-participants, signaling decentralized adoption. While cutting diesel reliance, integrating biomass systems remains critical for sustainability. The growing use in the DRC underscores the technology’s scalability and transformative potential for cassava value chains, offering cost efficiency and quality improvements.